LIBERALISM WITHOUT a PRESS: EIGHTEENTH-CENTURY MINAS GERAES AND THE ROOTS OF BRAZILIAN DEVELOPMENT - Pait, Heloisa [UNESP]; Brienza, C.; Robinson, L.; Wellman, B.; Cotten, SR; Chen, W. (Emerald Group Publishing Ltd, 2019)
This chapter introduces the important connections between media, democracy, and development in Brazil. Brazilian thought has relied heavily on conceptual oppositions in attempts to understand the country, as if there were something mysteriously contradictory in our culture and history, forever set on a rift between modernity and tradition. However convincingly described, the origin of such oppositions has never been fully explained. Introducing media history and theory into this discussion, we present a material dichotomy that illuminates the more abstract and cultural explanations of our particular history. We look at the region of Minas Geraes, where a sophisticated and diverse culture developed after the gold rush in the eighteenth century, in the Americas, and contrast such cultural achievements with the insurmountable difficulties in establishing a compatible written culture, primarily due to the prohibition of printing in the colony. We take note of the particular experience of the Conversos in Brazil, Jews who adopted Christianity in the shadow of the Portuguese Inquisition, as key to understand our ambivalent relationship to the written word and to knowledge. We describe commercial and cultural networks and contrast them with the paucity of media networks, including those of books and mail, domestic and international. This material disconnect, constitutive of colonial times in general, was particularly important during the formative years of a national market and identity and continues to resonate in the present.
Keywords: Brazil; development; freedom of the press; liberalism; literacy; Portuguese inquisition